2022
DOI: 10.3389/fenvs.2022.860786
|View full text |Cite
|
Sign up to set email alerts
|

Nano-TiO2 Adsorbed Decabromodiphenyl Ethane and Changed Its Bioavailability, Biotransformation and Biotoxicity in Zebrafish Embryos/Larvae

Abstract: Decabromodiphenyl ethane (DBDPE), a novel brominated flame retardant, may co-exist with other pollutants including nanoparticles (NPs) in aquatic environment. Due to structural similarity with decabromodiphenyl ether, DBDPE has been reported to exhibit thyroid disrupting effects and neurotoxicity. This study further evaluated the behavior of DBDPE in aqueous environments along with the bioavailability and toxicity of DBDPE in aquatic organisms in the presence of TiO2 nanoparticles (n-TiO2). When co-existing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…In addition, the average free-swimming speed during the dark–light transition period was significantly increased in all light and dark phases upon 400 μg/L DBDPE exposure (Figure A). These observations were consistent with previous studies, which reported excitatory effects in zebrafish larvae upon embryonic exposure to DBDPE. , …”
Section: Results and Discussionsupporting
confidence: 94%
“…In addition, the average free-swimming speed during the dark–light transition period was significantly increased in all light and dark phases upon 400 μg/L DBDPE exposure (Figure A). These observations were consistent with previous studies, which reported excitatory effects in zebrafish larvae upon embryonic exposure to DBDPE. , …”
Section: Results and Discussionsupporting
confidence: 94%
“…Meanwhile, the hyperactivity of larvae was observed during both light and dark cycles (Figure B,D). In our recent study, acute exposure to 10 nM DBDPE also caused significantly increased contents of neurotransmitters (GABA, ACh, choline, and NE) and increased locomotor speed in zebrafish larvae . These results suggested that DBDPE exposure may cause multigenerational effects on the homeostasis of neurotransmitters in zebrafish larvae.…”
Section: Resultsmentioning
confidence: 76%
“…Fish and marine mammals DBDPE could be rapidly metabolized (39.6-66.6 pmol in 90 min) to phenolic metabolites by marine mammal liver microsomes from arctic areas (polar bear, beluga whale, and ringed seal) [101] . DBDPE debromination (7 unknown compounds) was also confirmed in zebrafish after water-borne exposure [102] . They tentatively assigned them to nona-BDPE, nona-brominated products, octa-BDPE, hepta-BDPE, and other-brominated products [103] .…”
Section: Birdsmentioning
confidence: 88%